Impact of gender diversity of corporation on firm's performance: a comparative study of the UK and the USA - Zhao, Xiya (2020)
This paper adopts quantitative research to analyze the relationship between gender diversity and corporate performance. We use data from 280 UK listed companies and U.S. listed companies respectively which are retrieved from Bloomberg. The results show that gender diversity is not correlated with UK corporate performance and is negatively correlated with firm performance in rare cases. Gender diversity has little impact on US corporate performance and in rare cases it is positively correlated with firm performance in the U.S.